Added Effect of Pratimarsha Nasya with Ksheerabala Taila (14 Aavartita) over Selected Yoga Techniques in Insomnia - Vrinda V,; V K Sunitha,; Sajitha Bhadran, (International Journal of Ayurveda and Pharma Research, 2023)
Insomnia is a prevalent psycho physiological sleeping disorder, included in the International Classification of Sleep Disorders-2 (ICSD-2). By definition insomnia is a difficulty in initiating or maintaining sleep, or both or the perception of a poor quality sleep. Insomnia leads to various social, interpersonal and occupational impairments. Clinical studies have proven that Yoga is effective in insomnia. Present study was to find out the added effect of Pratimarsha nasya with Ksheerabala taila (14 Aavartita) over selected Yoga techniques in relieving insomnia. As per Acharya Susrutha in Chikitsa Sthana, doing Pratimarsha nasya daily during evening hours (Sayamkala) renders Sukhanidraprabhodanam. A pre-post interventional study was performed in 40 participants both male and female, satisfying the inclusion and exclusion criteria. Out of 40 participants, 20 each were randomly allocated to Group I and Group II. In Group I, Pratimarsha nasya using Ksheerabala taila (14 Aavartita) was administered 1ml in each nostril at evening time along with the practice of selected yoga techniques during morning hours. In Group II, only selected Yoga techniques were advised. The study period was for 30 days. The pre & post changes in mean score value was assessed using Pittsburgh Sleep Quality Index (PSQI) score. The data was analyzed using unpaired t test, and was statistically significant with a p value ≤0.01. Thus the added effect of Pratimarsha nasya with Ksheerabala taila (14 Aavrtita) over selected Yoga techniques in insomnia is more effective than selected Yoga techniques alone.